Bullying and victimization in children with special educational needs: implications for inclusive practices - Didaskalou, Eleni; Andreou, Eleni; Vlachou, Anastasia (Revista Interacções, 2009)
Bullying has been recognized as a widespread, persistent and serious problem occurring in schools across different national contexts. Despite the surge of interest in bullying in recent years, much of the research has focused on its multiple facets and characteristics among non-disabled students, while little is known about its incidence and dimensions in the population of students receiving special education support provision. It is well-known that schooling has generally been constructed and operates around the notions of normalization and homogeneity and children’s diversity often generates discriminating responses contributing to exclusionary educational experiences. In the light of above, the present study aims at exploring the extent and different types of bullying and victimization among Greek students receiving special education support provision. The sample of the study consisted of 173 students attending 5th and 6th primary school grades and participating in pull-out special education delivery programs operating within mainstream schools. According to the findings, participants were actively involved in both bullying and victimization with higher rates in victimization. Bullying was mainly related to physical aggressiveness, humiliating and racist behaviors towards others and social isolation from peers, while victimization included destruction of personal belongings and being attacked. Statistically significant differences were identified between girls and boys over the different types of bullying and victimization getting involved in, with girls experiencing mostly social isolation and manipulation from others and boys displaying aggressiveness towards others and attacking peers. Statistically significant differences were also found in physical bullying between children receiving more than 12 hours a week special education support and the rest. Children with developmental disabilities tended to use more indirect methods of bullying such as social exclusion more often than children with learning difficulties and children with learning difficulties combined with socio-emotional behavioral disorders. Overall bullying behavior was found to be predicted by presence of playmates during playtime and victimization by absence of playmates during break and limited number of friends in class. The implications of the study for developing school-based inclusive responses to students with SENs, are also discussed.